2018
DOI: 10.1037/pst0000169
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association between patients’ early treatment outcome expectation and their posttreatment outcomes.

Abstract: Patients’ outcome expectation (OE) represents their belief about the mental health consequences of participating in psychotherapy. A previous meta-analysis of 46 independent samples receiving the treatment of at least 3 sessions revealed a significant association between more optimistic baseline, or early treatment, OE and more adaptive posttreatment outcomes (weighted r = .12 or d = .24; Constantino, Glass, Arnkoff, Ametrano, & Smith, 2011). The present study represents an update to that meta-analysis. To be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
193
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(216 citation statements)
references
References 123 publications
15
193
2
6
Order By: Relevance
“…Predictive and convergent validity of the motivation scale has been established in previous studies (Barth et al, 1988;Høglend et al, 1992). Studies have shown that motivation /positive expectations have been found to be a strong predictor of outcomes (see Constantino et al, 2018). In our study, motivation showed to be a moderator of outcome: Highly motivated patients showed a better long-term positive effect of transference work compared to those with low motivation (Marble et al, 2011).…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Predictive and convergent validity of the motivation scale has been established in previous studies (Barth et al, 1988;Høglend et al, 1992). Studies have shown that motivation /positive expectations have been found to be a strong predictor of outcomes (see Constantino et al, 2018). In our study, motivation showed to be a moderator of outcome: Highly motivated patients showed a better long-term positive effect of transference work compared to those with low motivation (Marble et al, 2011).…”
Section: Methodssupporting
confidence: 69%
“…On the other side of the spectrum, we were also interested in investigating how a resourceful aspect of the patient's pretreatment functioning might affect the therapist's CT. Our chosen variable for this purpose was motivation for psychodynamic treatment which was operationalized in terms of a desire for self-understanding and change, and reasonable expectations about what can be achieved in therapy. Variants of this construct (i.e., positive and realistic expectations of change) have been demonstrated to constitute a salient predictor of outcomes across theoretical perspectives (for a summary, see Constantino et al, 2018). It would be expected that motivation is related to less negative and/or more positive CT in therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, compared to personality characteristics, which tend to remain stable over time, expectations are more variable (Constantino et al., ). In Study 4, the two‐week test–retest reliabilities, although statistically significant, were modest (ranging from .31 to .49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a review of this research concluded that “expectations may be even more vital to the psychotherapy process than is often acknowledged” (Greenberg, Constantino, & Bruce, , p. 657). Since positive expectations—for example, that therapy will be helpful, that the process will be smooth—contribute significantly to the success of individual psychotherapy (Constantino, Visla, Coyne, & Boswell, ), we reasoned that due to the complexity of romantic partnerships, expectancies are likely to be just as influential in couple therapy, if not more so. For instance, each of the women in the preceding examples spontaneously told the therapist how she expected the process to unfold.…”
mentioning
confidence: 99%
“…Having established that psychotherapy works well for most common mental health problems (Norcross & Lambert, 2018), and better than many other evidence-based medical practices (Wampold & Imel, 2015), we are also getting closer to understanding why psychotherapy works across different approaches. Some of the (pan-theoretical) process factors with the most promising evidence thus far are; a sound alliance between therapist and client (Flückiger et al, 2018); collecting and giving feedback on client progress using routine outcome monitoring (Lambert et al, 2018); therapist empathy (Elliott et al, 2018), facilitative interpersonal skills (Anderson et al, 2009) and cultivating client positive expectations (Constantino et al, 2018).…”
mentioning
confidence: 99%